Fisioterapia post operatoria en la enfermedad de Dupuytren - Andrade Ipiales, David Alejandro (2022)
ABSTRACT: “Postoperative physiotherapy in Dupuytren’s disease” is an important area of intervention within the field of Physiotherapy, the Frenchman Guillaume Dupuytren in 1831 describes the pathology as a fibromatosis located in the palmar aponeurosis, progressive and leading to deformation in flexion, with surgical management being the most used treatment and physiotherapy as a postoperative treatment to achieve the improvement of the patient. The objective of this research was to know the postoperative physiotherapeutic treatments in Dupuytren’s disease to determine the effects achieved in patients, by collecting information from bibliographic sources. The methodological approach of the study was descriptive because the veracity of the scientific articles corresponding to Dupuytren’s disease was analyzed, eligible articles had to meet the criteria identified by the PEDro scale, which included 35 studies. Literature review found data on postoperative treatment in Dupuytren’s disease since different modalities are found; that help the recovery of people with Dupuytren’s disease, being an effective and safe invasive treatment to reduce pain in the early nodular stage of Dupuytren’s disease. With the research carried out, the different treatments that are applied as postoperative physiotherapy were known and the benefits of reintegrating patients into their activities of daily living, achieving more independence. Some treatments on pathology such as the use of ultrasound, the application of frictional massage. A heat treatmentwith joint stretching and paraffin helped above all to the recovery of the extension of the affected joints generating a softening and increasing the extensibility of fibrous tissue, positively improving the range of motion.